Activating The Capacity of Deconstruction of Long Narrative Texts Through Cinematic-Auditory Hibrida Media: An Empirical Study of The Analysis of The Novel "Bumi Manusia" in Intermediate School - Vitania Barantika Delly Yanti; Jayanti; Febriyani Hutasuhut; Erlinda Nofasari; Rahmat Kartolo (International Journal of Educational Research Excellence (IJERE), 2026)
Literary appreciation learning in the context of long texts faces substantial challenges in the form of limited instructional time, decreased student concentration capacity, and the absence of alternative media that can convert long narrative complexity into accessible representations. This study explores the use of a synergistic combination of visual cinematic media and auditory narrative in learning the structural analysis of Pramoedya Ananta Toer's novel Bumi Manusia (This Earth of Mankind) among a population of eleventh-grade students in general secondary education. Using a qualitative-descriptive investigative approach involving thirty-two (n=32) students, the study explores the phenomenon of narrative comprehension reconstruction, penetration of the novel's constitutive elements, and transformation of analytical comprehensiveness after exposure to the first and second parts of the audiobook series from the YouTube platform. Significant findings indicate that the combined visual-auditory medium produces an accuracy of identification of complex narrative elements reaching 95% in the categories of characters, socio-historical settings, and psychological changes of the protagonist. The methodological aspects of hybrid medium-based learning show a significant increase in participants' capabilities for close reading and layered interpretation of polysemic thematic substances. Seventy-eight percent of participants achieved a deep level of analysis, integrating the sociopolitical context of the work with the narrative dimension at a sophisticated level. The study's conclusions recommend adopting a hybrid media approach as a valid and efficient pedagogical strategy for teaching long-form novels, particularly in educational settings with limited raditional learning infrastructure. The study's implications highlight the need for collaboration between the digital content industry and educational institutions to produce learning media that meet pedagogical standards and are economically accessible